Investigação das práticas de logística urbana em cidades brasileiras - Dias, José Maria (2017)
With the growth of urban population and the increase of the vehicle fleet, Brazilian cities face urban dysfunction problems like congestion, environmental pollution, car accidents among others and its consequences are felt by citizens. With the institution of the PNMU - Política Nacional de Mobilidade Urbana (National Urban Mobility Policy), Brazil has sought to direct the planning of solutions for the urban transportation of people and cargo in an integrated and sustainable way The literature shows a lack of national research focused on planning and local policies of urban freight and better understanding of the authorities on the freight transportation and supply chains, for decision-making on policy and planning Urban Freight Transport (UFT). The practices and concepts of City Logistics intend optimal solutions for goods handling issues in urban areas. In this context, the use of City Logistics (CL) practices in Brazilian cities was investigated. Therefore, the contents related to UFT and CL were analyzed in the PlanMobs – Planos de Mobilidade Urbana (Urban Mobility Plans) elaborated by these cities. Additionally was produced a data collection (survey research), with those responsible for the preparation/review of PlanMobs. This research identifies the resources used in the UFT planning, the CL practices adopted and the perceptions of the municipal authorities about the UFT and CL. The results showed that the LU is still neglected and appears not to be the focus of the authorities who have developed the PlanMob. The lack of local authorities’ specific skills, with the low use of planning resources makes it impossible to achieve the LU goals.